Phaseolus angucianae (Leguminosae: Phaseoleae), a new bean species from Fila cruces of Southeastern Costa Rica - Debouck, Daniel G.; Araya Villalobos, Rodolfo; Chaves-Barrantes, Néstor Felipe (Botanical Research Institute of Texas, 2018)
A new wild bean found in the mountainous range "Fila Cruces" of southeastern Costa Rica is described. To date, only four populations are known from different sites on the slopes of Cerro Anguciana and "Fila Cruces" where it seems to be endemic. The differences (slender curved racemes, small oval acuminate primary and pedicelar bracts, lilac inner face of standard, white wings) are presented with closely related species such as P. hygrophilus and P. oligospermus of the section Brevilegumeni to which it may belong.